Efektivitas Pupuk Daun terhadap Pertumbuhan dan Hasil Kedelai pada Sistem Tanpa Olah Tanah - Dewi Auliya Ulva; Supriyono Supriyono; Pardono Pardono (Universitas Sebelas Maret, 2019)
Maintaining soil quality can be done by cultivating soybean using the conservation soil tillage principle, which can be applied in no tillage soil system. The purpose of this study was to obtain the influence of the type of leaf fertilizer and the frequency of leaf fertilizer application on the growth and yield of soybeans in the without tillage system. This research was conducted in Kedawung, Sragen Central Java on May-August 2018. The research used randomized complete block design (RCBD) with 7 levels and 4 replications. Foliar fertilizer was given every 10 and 15 days. The observed variables were periodic observations, maximum vegetative, and yield. Maximum vegetative and periodic observations showed that P3 (gandasil D fertilizer every 15 days) has significant effect and resulted the highest yield. The results of the study showed that gandasil D fertilizer every 15 days treatment increased leaf area index. Gandasil b every 15 days treatment increased the yield of 100 seeds, but reduce the quantity of seed weight/plot, and foliar fertilizer is not effectively used in this cultivation.